Formation of the trend of ecologically safe social environment - an important component of sustainable development (on the example of tourism) - Garashchuk, Olena; Kutsenko, Vira (Herald of Economics, 2021)
Introduction. A characteristic feature of our time is the deterioration of the ecological situation, necessitating the formation of an ecologically safe environment as an important component of sustainable development. In this regard, the tourism sector and ecological tourism in particular, which is one of the leading types of economic activity that provide an ecological direction of economic development, is gaining momentum. Today there are both favorable and unfavorable factors for the development of the tourism sector.Purpose of the research. The study is devoted to the substantiation of the scientific and practical foundations, the application of which will ensure the activities of the tourism sector in the context of the implementation of the environmental requirements of sustainable development.Results. The essence and significance of an ecologically safe social environment, necessary to ensure sustainable development in the country, is revealed. It highlights the place in this process of the tourism sector in general and ecological tourism, in particular, as well as the types of natural resources on the basis of which this area operates. A vision of the main functional areas of activity in the field of ecological tourism and infrastructure components of the tourism industry is presented.The main attention in the aspect of the investigated problematics is paid to the search for ways of preserving and rational use of natural resource potential. At the same time, special emphasis is placed on environmental education – primarily children, adolescents, youth and the substantiation of the main tasks of environmental policy in the context of ensuring sustainable development. Problems associated with the impact of the environmental situation on the state of public health are also taken into account. The proposed theoretical and methodological approaches to the formation of a trend to further strengthen the relationship between ecology, economy and society in the context of the implementation of European environmental standards in national legislation.Perspectives. Further research is required on the issues of determining the directions of specific measures for the development of the tourism sector, carried out taking into account the existing socio-economic prerequisites and aimed at creating an ecologically safe social environment as an important component of sustainable development.